Stress, Coping and Social Supports in the Adolescent Years - Intan Hashimah Mohd. Hashim , (Kajian Malaysia, 2007)
This paper results from a study that was conducted on 209 Form Four students from two schools in Penang. In this study, a semi-structured interview covering questions on demographics, a 12-item measure of self-esteem, and a 20-item measure of well-being was conducted. Students were also asked to report their Penilaian Menengah Rendah (PMR) results as an indicator of their academic performance. To assess stress, coping and social supports, respondents were given a list of possible stressors (e.g., problems with relationships at home and school) and were asked to indicate whether or not they were bothered by these stressors, the type of coping that they had used in dealing with these stressors, and the type of social supports that they had received in relation to these stressors. A higher proportion of respondents (77%) identified issues related to academics and lessons as a problem compared to other issues (relationships at home, 34%, and relationships at school, 31%). The number of stressors related to everyday life was significantly related to well-being, but not to self-esteem or academic performance. Respondents reported a variety of problem-specific coping. Supports received were also problem-specific in nature. The findings have both applied and theoretical implications.